Heparin-Associated Thrombocytopenia: The Antibody Is Not Heparin Specific - Greinacher, A; Michels, I; Mueller-Eckhardt, C (Thrombosis and Haemostasis, 1992)
In this study the hypothesis was assessed whether heparin-associated thrombocytopenia (HAT) may be caused by an antibody dependent on polysulfated oligosaccharide epitopes, present not only on heparin but also on different polysulfated substances such as dextran sulfate and pentosan polysulfate. We found that the major factor for eliciting platelet activation with sera of HAT type II patients is neither the structure nor the AT III binding capacity of an oligosaccharide, but rather its grade of sulfation. This was shown by in vitro crossreactivity studies with 40 sera of HAT type II patients using unfractionated heparins, LMW heparins (Fragmin, Fraxiparin), enoxaparin, LMW heparinoid (Org 10172 and its subfractions), de-N-sulfated heparin, dermatan sulfate, dextran sulfate, pentosan polysulfate and dextran. Platelet activation was measured by the heparin induced platelet activation (HIPA) assay and the serotonin release assay (SRA). The platelet activating factor was isolated with the IgG fraction, but did not bind to heparin and dextran sulfate fixed to a solid phase. By isoimmune fixation electrophoresis a monoclonal gammopathy was ruled out in the three sera assessed. The in vivo effect of different LMW heparins and the heparinoid Org 10172 was observed in 10 patients with HAT type II. In a prospective study, a compatible heparin-like anticoagulant was selected for 10 HAT patients for whom further parenteral anticoagulation was required. The only substance that showed no crossreactivity in vitro was the LMW heparinoid Org 10172, which differs from heparin and LMW heparins by its low-grade sulfation. Upon treatment with the heparinoid, all 10 patients had a good clinical outcome, even if they had previously developed thromboembolic complications under LMW heparin administration. As Org 10172 contains a small amount of a LMW heparin-like substance (3%) this heparinoid should not be used in HAT patients without prior in vitro testing. We conclude that heparin-associated thrombocytopenia is not caused by a heparin-specific antibody and that a major factor contributing to the pathomechanism is the high grade of sulfation present in a variety of polysulfated oligosaccharides.